Pressure swing adsorption of Li exchange hierarchical X zeolite for pure hydrogen from binary gas mixture - Shrotri, Aadesh R.; Birje, Amit R.; Nandanwar, Sachin U. (International Journal of Hydrogen Energy, 2024)
This study reports the separation of pure hydrogen (H2) employing pressure swing adsorption (PSA). The Li-X and Li-hierarchical X (Li-H-X) zeolite were prepared by an ion exchange process. The sorbents were evaluated through several experiments including, breakthrough, empty bed contact time (EBCT), single-bed, and two-bed PSA with different steps. The effect of pressure, purity, and recovery relationship was developed. The highpressure PSA study was performed at 4, 6, and 10 bar with varying feed flow rates to assess their efficacy in pure H2 separation using binary gas stream (H2/CO2, 75/25 vol.%). The breakthrough adsorption capacity of Li-H-X exhibited 3.4 mmol g-1 and 0.212 mmol g-1 of CO2 and H2, respectively. Li-H-X shows -8% higher CO2 sorption capacity than the Li-X sorbent at 1 bar and 300 K due to the large meso-microporous structure of the sorbent. The two-bed PSA purity and recovery were found higher than single-bed PSA. Using two-bed PSA, the Li-H-X achieved a 99.5% of purity, 92.9% of recovery, and 10.4 mL min-1 g-1 of productivity, which was -16% higher recovery and productivity than single-bed PSA at a flow rate of 1200 mL min-1 at 6 bar. With increasing the pressure and flow rate, the recovery of Li-H-X was enhanced up to 93.7% with 99.1%-99.9% H2 purity. The long-term PSA was run using Li-H-X sorbent for 7.5 h with 230 cycles with H2 purity between 98.5 and 99.5% at 6 bar. Interestingly, the adsorbent shows the scalability of PSA for efficient H2 separation for a binary mixture of H2/CO2.
Keywords: adsorbent; Binary gas mixture; Hydrogen purification; Li-H-X; Mesoporous zeolite; Pressure swing adsorption